On the use of the Gaussian approach for the performance evaluation of direct-detection OFDM receivers impaired by in-band crosstalk - Rebola, J. L. (2022)
The Gaussian approach (GA) is used to assess the impact of in-band crosstalk on the performance of direct-detection orthogonal frequency division multiplexing (OFDM) optical communication systems. The GA accuracy is compared with estimates of the bit error probability (BEP) and crosstalk penalty obtained using Monte Carlo (MC) simulation. The GA revealed a reduced accuracy when estimating the BEP. However, when estimating the 1 dB crosstalk penalty, the GA exhibited a good accuracy (less than 0.5 dB in comparison with the crosstalk level estimated using MC simulation), for 16-quadrature amplitude modulation (QAM) and 64-QAM mappings in the OFDM subcarriers. The GA leads to very discrepant estimates of the crosstalk penalty for high crosstalk levels.